An Exploration into the Development of Entrepreneurship Education in Secondary Education Policy - Oji, Uchechi C. (2012)
The purpose of this study was to explore the development of entrepreneurship education in secondary education policy. In Nigeria, entrepreneurship education is a new and developing area which has been recently introduced to its education policy. In order to explore how this field can be developed by the country an analysis was made of Junior Achievement Worldwide (JAW) as well as its partner companies; Young Enterprise Scheme (YE), United Kingdom and Junior Achievement- Young Enterprise (JA-YE), Europe. These case studies were chosen because they represent an all encompassing model of entrepreneurship education which is offered to young people (4-25 years). A qualitative research of these cases were made to highlight key processes that have been applied in its programmes; namely personal development, entrepreneurial thinking, business formation and management and relevant partnerships. These key processes were offered as a result of prior literature review which gave insight to them as what entrepreneurship education entails. The findings from the case study further revealed that applying personal development and entrepreneurial thinking training to the students in addition to knowledge and hands-on experience on how a business is operated was very critical to the success of its programme. The organisations also made relevant partnerships with the business community, volunteers and voluntary financiers, that boosted its development of a thorough curriculum, aided its delivery and provided students with contact with industry experts. It is recommended that the Nigeria adopt these key processes to ensure that its investment in the entrepreneurial capabilities of its youth is effectively harnessed.